Society Participation, Transparency, Public Policy Accountability and Board Knowledge on Monitoring of School Revenue and Expenditure Budgets - Eleuwarin, Usman; Muslim, Muslim (Advances in Economics & Financial Studies, 2024)
Purpose: This research aims to determine the influence of Society Participation, transparency, public policy accountability, and board knowledge on monitoring school revenue and expenditure budgets. Study design/methodology/approach: The population in this study included school principals, all teachers, staff, school committees at state high schools in Makassar City, and Commission E members of the DPRD of South Sulawesi Province. A sample of 50 people was selected using random sampling techniques. Data collection was conducted through observation, questionnaires, and literature study. Descriptive statistical analysis and multiple linear regression analysis using SPSS were used to analyze the data. Findings: The results of this research indicate that both simultaneously and partially, the variables of Society Participation, transparency, public policy accountability, and board knowledge do not have a significant effect on the supervision of school revenue and expenditure budgets in public high schools in Makassar City. Originality/value: This research contributes to the existing literature by examining the influence of Society Participation, transparency, public policy accountability, and board knowledge on the monitoring of school revenue and expenditure budgets. The findings suggest that other factors may play a more significant role in supervising these budgets in public high schools in Makassar City.